An Ethnographic Study of Preservation Strategies of the Kun Traditional House in Sarmi, Papua - Anggia Riani Nurmaningtyas; Yudha Yapsenang; Muh Jundullah D Ulhaq; Sugito Utomo (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2025)
This study presents an ethnographic exploration of the Kun House, the traditional dwelling of the Armati community in Sarmi Regency, Papua. The Kun Households have profound symbolic and spiritual significance, reflecting social relations and human–environment interactions within traditional settlements. However, modernization, through changes in livelihoods, the introduction of new materials, and the expansion of infrastructure, has transformed settlement patterns and diminished the socio-spatial role of the Kun House. Fieldwork conducted in Binyer Village, East Sarmi District, employed a qualitative approach grounded in architectural anthropology, combining interviews with community leaders, participant observation, spatial documentation, and archival analysis. The findings reveal community-based and policy-supported strategies for safeguarding the Kun House as part of sustainable settlement planning. This study highlights the importance of integrating cultural heritage values into contemporary development to preserve the Armati community’s identity amid socio-economic transitions.